Analisis Pengaruh Earnings Per Share, Inflasi, dan Suku Bunga Terhadap Return Saham - Latifah Choirunnisa' Kusuma Wardani; Novera Kristianti Maharani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to understand the effect of earnings per share, inflation, and interest rates on stock returns. This study utilizes a collection of companies consistently listed on the Indonesia Stock Exchange from 2022 to 2024. Data for this study is sourced from annual reports, the Consumer Price Index (CPI), and the BI rate. The sampling technique used was purposive sampling, and data from 138 companies were obtained. This study used measurements of earnings per share (annual EPS), inflation (annual inflation rate), and interest rates (average annual interest rate). This data was processed using linear regression analysis with Stata software. The results of this study indicate that earnings per share has a positive and significant effect on stock returns, while inflation and interest rates have a negative and significant effect on stock returns.